1993
DOI: 10.1084/jem.177.5.1461
|View full text |Cite
|
Sign up to set email alerts
|

Selective immunosuppression by administration of major histocompatibility complex class II-binding peptides. II. Preventive inhibition of primary and secondary in vivo antibody responses.

Abstract: SummaryThe self-mouse lysozyme peptide corresponding to residues 46-62 (ML46-62) binds to the major histocompatibility complex (MHC) class II molecules I-A k and it selectively inhibits, when coinjected with antigen, priming of I-Ak-restricted, antigen-specific T cells. We demonstrate that administration of ML46-62 also inhibits in vivo antibody responses induced by I-A krestricted T helper cells. ML46-62 is able to prevent the primary anti-hen egg white lysozyme (HEL) antibody response induced by the entire H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1994
1994
2001
2001

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 42 publications
(42 reference statements)
0
7
0
Order By: Relevance
“…The Antigen-presenting Activity in Immune LNC Is Restricted to the Low Buoyant Density Population. We have previously shown that APC in draining lymph nodes from mice immunized subcutaneously with HEL in adjuvant display antigenic complexes formed in vivo between peptides derived from HEL processing and class II molecules (19,20). After immunization with HEL in IFA or CFA, antigenic complexes are readily detectable on lymph node APC from day 2 to 14 after immunization (not shown).…”
Section: Resultsmentioning
confidence: 92%
“…The Antigen-presenting Activity in Immune LNC Is Restricted to the Low Buoyant Density Population. We have previously shown that APC in draining lymph nodes from mice immunized subcutaneously with HEL in adjuvant display antigenic complexes formed in vivo between peptides derived from HEL processing and class II molecules (19,20). After immunization with HEL in IFA or CFA, antigenic complexes are readily detectable on lymph node APC from day 2 to 14 after immunization (not shown).…”
Section: Resultsmentioning
confidence: 92%
“…However, T cells selected by immunization and in vitro clonal expansion driven by T‐ag in SVT2nuc would be expected to respond at least as well to SVT2nuc as free T‐ag. The weaker proliferative responses of SVT2nuc immune T cells may be explained by limited presentation of processed T‐ag peptides due to competition with peptides derived from other proteins present in SVT2nuc [28–30]. This competition between T‐ag‐derived peptides and other peptides could, in turn, have limited the activation and clonal expansion of T‐ag‐specific T cells in vivo and in vitro .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that blockade of MHC binding could inhibit T cell activation and Ab production in response to stimulation by antigenic peptides in vivo [22,23]. As shown in Figs.…”
Section: Discussionmentioning
confidence: 85%